A mouse speciation gene encodes a meiotic histone H3 methyltransferase - Mihola, Ondrej; Trachtulec, Zdenek; Vlcek, Cestmir; Schimenti, John C; Forejt, Jiri (Science (New York, N.Y.), 2009)
Speciation genes restrict gene flow between the incipient species and related taxa. Three decades ago, we mapped a mammalian speciation gene, hybrid sterility 1 (Hst1), in the intersubspecific hybrids of house mouse. Here, we identify this gene as Prdm9, encoding a histone H3 lysine 4 trimethyltransferase. We rescued infertility in male hybrids with bacterial artificial chromosomes carrying Prdm9 from a strain with the "fertility" Hst1(f) allele. Sterile hybrids display down-regulated microrchidia 2B (Morc2b) and fail to compartmentalize gammaH2AX into the pachynema sex (XY) body. These defects, seen also in Prdm9-null mutants, are rescued by the Prdm9 transgene. Identification of a vertebrate hybrid sterility gene reveals a role for epigenetics in speciation and opens a window to a hybrid sterility gene network.
Keywords: vznik druhů (genetika); Epigenesis, Genetic; testis; Crosses, Genetic; Hybridization, Genetic; Mice, Transgenic; histony; regulace genové exprese; Molecular Sequence Data; mužská infertilita; molekulární sekvence - údaje; Female; myši transgenní; Histone-Lysine N-Methyltransferase; myši inbrední C3H; Mice, Inbred C3H; Meiosis; zvířata; myši; hybridizace genetická; Methylation; křížení genetické; Mice; Amino Acid Sequence; epigeneze genetická; meióza; ženské pohlaví; Gene Expression Regulation; metylace; Male; Testis; histonlysin-N-methyltransferasa; Histones; Chromosome Mapping; ovarium; Infertility, Male; Genetic Speciation; Chromosomes, Artificial, Bacterial; mapování chromozomů; Animals; Ovary; mužské pohlaví; umělé bakteriální chromozomy; sekvence aminokyselin